Permanence in a Discrete Mutualism Model with Infinite Deviating Arguments and Feedback Controls - Changjin Xu; Yusen Wu (Discrete Dynamics in Nature and Society)
We propose and deal with a discrete mutualism model with infinite deviating arguments and feedback controls. Sufficient conditions which guarantee the permanence of the system are obtained by using the difference inequality theory. The paper ends with brief conclusions.